Pengembangan Sumber Daya Manusia Aparatur Desa: Upaya Mewujudkan Pelayanan Prima - Riewpassa, Abraham; Latuheru, Belianus Patria; Touwely, Godprit Haris (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2025)
This study aims to explore the development of human resources (HR) in the administration of Makububui Village, Taniwel Subdistrict, focusing on three key aspects: basic competencies, management skills, and technical abilities, in the effort to achieve exemplary public service. The research method employed is qualitative, utilizing in-depth interviews and document analysis, involving village officials and relevant stakeholders to gain a comprehensive understanding of the HR capacity in the village. The findings indicate that a strong understanding of regulations and village authority is crucial for enhancing service effectiveness. Moreover, good management skills contribute to fostering a positive working culture among village administrators, while the enhancement of technical abilities, particularly in administration and public service, improves efficiency and responsiveness to community needs. This research provides valuable insights into strategies for developing HR capacity in village administration, ultimately aiming to improve the quality of public services sustainably.